2019
DOI: 10.1159/000496494
|View full text |Cite
|
Sign up to set email alerts
|

Very Preterm Infants with Technological Dependence at Home: Impact on Resource Use and Family

Abstract: Objective: To examine the impact of medical complexity among very preterm infants on health care resource use, family, and neurodevelopmental outcomes at 18 months’ corrected age. Methods: This observational cohort study of Canadian infants born < 29 weeks’ gestational age in 2009–2011 compared infants with and those without medical complexity defined as discharged home with assistive medical technology. Health care resource use and family outcomes were collected. Children were assessed for cerebral palsy, dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Clinicians carry professional obligations to present balanced information, to not only elicit family values but to also consider offering professional guidance and medical recommendations regarding escalation of technology unique for each child's circumstance (Wilfond, 2014). Technology advancement warrants open conversation about not only the mechanisms of a tracheostomy or home ventilator, but also open discussion on the impact to family sleep patterns and sustained parental employment due to hands‐on care needs for the child in order for families to make truly informed and insightful decisions (Hammer, 2000; Lazzarin, Schiavon, Brugnaro, & Benini, 2018; Nassel et al, 2019). While tracheostomy placement may seem like a straightforward surgical step, the procedure represents a significant shift in family caregiver duties and becoming “a semipermanent resident of the healthcare system, dependent on artificial support for survival” (Venkat, 2013).…”
Section: Otolaryngologymentioning
confidence: 99%
“…Clinicians carry professional obligations to present balanced information, to not only elicit family values but to also consider offering professional guidance and medical recommendations regarding escalation of technology unique for each child's circumstance (Wilfond, 2014). Technology advancement warrants open conversation about not only the mechanisms of a tracheostomy or home ventilator, but also open discussion on the impact to family sleep patterns and sustained parental employment due to hands‐on care needs for the child in order for families to make truly informed and insightful decisions (Hammer, 2000; Lazzarin, Schiavon, Brugnaro, & Benini, 2018; Nassel et al, 2019). While tracheostomy placement may seem like a straightforward surgical step, the procedure represents a significant shift in family caregiver duties and becoming “a semipermanent resident of the healthcare system, dependent on artificial support for survival” (Venkat, 2013).…”
Section: Otolaryngologymentioning
confidence: 99%
“…Centers may consider PSG to evaluate the need for pressure support in infants who have evidence of alveolar hypoventilation (more than 25% of the total sleep time with pCO 2 > 50 mmHg) 39 but it is unclear which infants with moderate to severe hypercapnia benefit from pressure support over supplemental oxygen. A Canadian retrospective cohort study identified that of infants born at GA < 29 weeks, only 0.9% and 0.6% were discharged on noninvasive ventilation (NIV) or tracheostomy ventilation respectively 40 . The indications for initiating NIV were not stated.…”
Section: Discussionmentioning
confidence: 99%
“…A Canadian retrospective cohort study identified that of infants born at GA < 29 weeks, only 0.9% and 0.6% were discharged on non-invasive ventilation (NIV) or tracheostomy ventilation respectively. 42 The indications for initiating NIV were not stated. After laryngomalacia, CNLD was the second most common indication for home CPAP over a period of 10 years at Westmead Children's Hospital.…”
Section: Discussionmentioning
confidence: 99%